Managing Gender Equality in Multinational Corporations : Finnish MNCs’ HRM practices in Japanese subsidiaries - Kisialiova, Nastassia (My University, 2020)
Human resource management is a key corporate function, prone to significant variation depending on the country of operation. Gender equality in particular varies across counties, with Japan ranking on the lowest spectrum among developed countries. Finland, on the other hand, is comparatively more advanced along with other Nordic countries. The purpose of this research is to understand how multinational corporations manage gender equality in their subsidiaries when the levels of equality are different in the home and host country environments. The study explores different understandings of gender equality, numerous human resource practices which concern gender equality, as well as mechanisms used to transferring practices and the impact of institutional environments on the outcome. The research methodology utilized in this study is qualitative. Data is gathered by conducting four semi-structured interviews with subsidiary HR representatives on location in Japan. Additionally, an expert familiar with work and life in both countries is interviewed for further contribution to evaluation of findings. The results of this study show that the Japanese subsidiaries of Finnish multinational corporations have a positive setting for gender equality, particularly when compared to the overall situation in Japan. Most significantly Finnish impact can be seen in work-life balance practices. These have emerged in the subsidiaries through interaction with Finnish colleagues and learning about the Finnish way of working and thinking. At the same time, Finnish headquarters are not actively part-taking in promotion of gender equality in their Japanese subsidiaries, and a gap exists between what is implemented in the two entities. There is more potential for the Finnish MNCs to promote gender equality and open the discussion in the subsidiaries than is currently done, as limiting beliefs among Japanese employees exist.

Henkilöstöjohtaminen on yhtiöiden keskeinen funktio, joka on altis huomattavalle vaihtelevuudelle riippuen toimintamaasta. Sukupuolitasa-arvo myös vaihtelee maittain ja kehittyneiden maiden kesken Japani on osoittautunut olevan heikoimmalla tasolla. Suomi on toisaalta muiden pohjoismaiden kanssa sukupuolitasa-arvoltaan edistyneimpiä maita. Tutkimuksen tarkoituksena on ymmärtää miten monikansalliset yhtiöt johtavat sukupuolitasa-arvoa tytäryhtiöissään, kun tasa-arvon tasot eroavat koti- ja kohdemaaympäristöissä. Tutkimuksessa käsitellään eri sukupuolitasa-arvon lähestymistapoja, lukuisia sukupuolitasa-arvoon liittyviä henkilöstöfunktioita sekä funktioiden siirtotapoja ja institutionaalisten ympäristöjen vaikutus siirtojen lopputulokseen. Tutkimus on toteutettu laadullisena tutkimuksena. Aineisto on kerätty toteuttamalla neljän tytäryhtiön henkilöstöjohtajan puolistrukturoitua haastattelua paikan päällä Japanissa. Lisäksi haastateltiin asiantuntijaa, jolla on kokemusta työstä ja elämästä molemmissa maissa, saadakseen lisänäkemyksiä löydösten tulkitsemiseksi. Tutkimuksen tulokset osoittivat, että suomalaisten monikansallisten yhtiöiden japanilaisilla tytäryhtiöillä on positiiviset lähtökohdat sukupuolitasa-arvolle, erityisesti verrattuna Japanin tilanteeseen. Erityisesti vaikutusta Suomesta näkyy työn ja elämä tasapainottamiseen liittyvissä käytännöissä. Nämä ovat ilmestyneet tytäryhtiöihin suomalaisten kollegoiden kohtaamisten kautta sekä oppimalla suomalaisesta työskentely- ja ajattelutavasta. Samalla, suomalaiset emoyhtiöt eivät kuitenkaan ota aktiivista otetta sukupuolitasa-arvon edistämiseen japanilaisissa tytäryhtiöissään, ja näiden kahden toimijan käytäntöjen välillä on eroja. Suomalaisilla monikansallisilla yhtiöillä on enemmän potentiaalia edistää sukupuolitasaarvoa ja avata keskustelua tytäryhtiöissään kuin tällä hetkellä tehdään, sillä rajoittavia uskomuksia japanilaistyöntekijöiden kesken on olemassa.
Keywords: Gender equality, human resource management, Japan